Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-2669
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Cognitive Processing Style Predicts Differences in Phonetic Imitation of Device and Human Voices

Abstract: Phonetic imitation, or implicitly matching the acousticphonetic patterns of another speaker, has been empirically associated with natural tendencies to promote successful social communication, as well as individual differences in personality and cognitive processing style. The present study explores whether individual differences in cognitive processing style, as indexed by self-reported scored from the Autism-Spectrum Quotient (AQ) questionnaire, are linked to the way people imitate the vocal productions by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…In a study of phonetic imitation between college roommates, Pardo et al (2012) found stronger alignment toward males (relative to females). The same asymmetry has been observed in studies directly comparing human and TTS voices: greater alignment toward male voices (both human and TTS) than female voices (Cohn et al, 2019;Snyder et al, 2019). Recently, a study comparing alignment toward identical TTS voices across three device platforms (varying in human-like embodiment) also showed this pattern (greater alignment toward the male voices, relative to female voices) (Cohn et al, 2020).…”
Section: Role Of Voice Gendermentioning
confidence: 63%
See 4 more Smart Citations
“…In a study of phonetic imitation between college roommates, Pardo et al (2012) found stronger alignment toward males (relative to females). The same asymmetry has been observed in studies directly comparing human and TTS voices: greater alignment toward male voices (both human and TTS) than female voices (Cohn et al, 2019;Snyder et al, 2019). Recently, a study comparing alignment toward identical TTS voices across three device platforms (varying in human-like embodiment) also showed this pattern (greater alignment toward the male voices, relative to female voices) (Cohn et al, 2020).…”
Section: Role Of Voice Gendermentioning
confidence: 63%
“…While Habler et al (2019) found no differences in participants' ratings of male and female TTS voices, other studies examining participants' speech behavior suggest there are some differences. For example, participants show different speech patterns toward male and female Apple Siri TTS voices, in similar directions as for real human male and female voices (Cohn et al, 2019;Snyder et al, 2019). This suggests that more subconscious behavior may reveal gender-mediated patterns (if present) in human-device interactions.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations